The challenges of anaerobic digestion and the role of biochar in optimizing anaerobic digestion. (March 2017) - Fagbohungbe, Michael O.; Herbert, Ben M.J.; Hurst, Lois; Ibeto, Cynthia N.; Li, Hong; Usmani, Shams Q.; Semple, Kirk T.
Graphical abstract: Highlights: Substrate induced inhibition. Acclimation of microbial cells to inhibition. Mechanisms of biochar adsorption and desorption. Impact of biochar on anaerobic digestion. Abstract: Biochar, like most other adsorbents, is a carbonaceous material, which is formed from the combustion of plant materials, in low-zero oxygen conditions and results in a material, which has the capacity to sorb chemicals onto its surfaces. Currently, research is being carried out to investigate the relevance of biochar in improving the soil ecosystem, digestate quality and most recently the anaerobic digestion process. Anaerobic digestion (AD) of organic substrates provides both a sustainable source of energy and a digestate with the potential to enhance plant growth and soil health. In order to ensure that these benefits are realised, the anaerobic digestion system must be optimized for process stability and high nutrient retention capacity in the digestate produced. Substrate-induced inhibition is a major issue, which can disrupt the stable functioning of the AD system reducing microbial breakdown of the organic waste and formation of methane, which in turn reduces energy output. Likewise, the spreading of digestate on land can often result in nutrient loss, surface runoff and leaching. This review will examine substrate inhibition and their impact on anaerobic digestion, nutrient leaching and their environmental implications, the properties and functionality of biochar material in counteracting these challenges.